Efektivitas Kegiatan Pekan Library sebagai Sarana Promosi Perpustakaan di UPT Perpustakaan Universitas Andalas - Rafnan, Eldiva; Marlini, Marlini (ARZUSIN, 2024)
A common problem that occurs in libraries is that some users do not know the function of the service and the use of collection materials. This can result in users being disinterested in using the library, unused collection materials piling up and taking up a lot of space and this is exacerbated by the COVID-19 pandemic which has caused a buildup of collection materials. This research uses quantitative research with descriptive methods with research instruments in the form of questionnaires. The sample studied was around 100 people with the Slovin formula. Data were analyzed through Respondent Achievement Target (TCR), normality test, linearity test, correlation test, hypothesis test, and coefficient of determination test carried out with SPSS 25. Respondent Achievement Target (TCR), normality test, linearity test, correlation test, hypothesis test , and the coefficient of determination test carried out with SPSS 25 from the research that has been carried out produces several conclusions that Effectiveness as variable x has an average TCR value of 76.9% which is categorized as Good and Library Promotion Facilities as variable y has an average TCR value amounting to 74.9% which is categorized as Fairly Good. Apart from the normality test which was not normally distributed, other tests succeeded in showing that Library Week activities were effective as a means of library promotion at the Andalas University Library. According to the coefficient of determination test, the value of the effectiveness of Library Week activities as a means of library promotion is 61.7%, which proves the effectiveness of Library Week activities to be used as a means of library promotion. The alternative hypothesis in this research is proven that there is an increase in the use of library resources at the Andalas University Library with the holding of Library Week activities.